Clinicopathologic Characteristics of Grade 2/3 Meningiomas: A Perspective on the Role of Next-Generation Sequencing - Kim, Junhyung; Hwang, Kihwan; Kwon, Hyun Jung; Lee, Ji Eun; Lee, Kyu Sang; Choe, Gheeyoung; Han, Jung Ho; Kim, Chae-Yong (Frontiers in Oncology, 2022)
Background: Grade 2/3 meningiomas have locally aggressive behaviors often requiring additional treatment plans after surgical resection. Herein, we explored the clinical significance of next-generation sequencing (NGS) in characterizing the molecular profiles of high-grade meningiomas. Methods: Patients with intracranial meningioma who underwent surgical resection in a single institution were retrospectively reviewed. Clinicopathologic relevance was evaluated using recurrence-free survival (RFS) as an outcome measure. NGS for the targeted gene regions was performed in 40 participants. Results: Among the 713 individuals in the study population, 143 cases (20.1%) were identified as having grade 2 or 3 meningiomas with a significantly lower female predominance. While the difference in RFS between grade 2 and 3 meningiomas was insignificant, a few conventional grade 2 cases, but with TERT promoter hotspot mutation, were highly progressive and refractory to the treatment. From the NGS study, recurrent mutations in TRAF and AKT1 were identified with a higher prevalence (17.5% and 12.5%, respectively) compared with grade 2/3 meningiomas reported in previous literature. However, their relations to other histopathologic properties or clinical factors were rarely observed. Conclusions: Grade 2/3 meningiomas show a broad spectrum of molecular profiles, as they have heterogeneous histologic characteristics.